Mechanisms of Social Movement Market Innovation: The Birth of the American Abortion Clinic - Halfmann, Drew (PARTECIPAZIONE E CONFLITTO, 2021)
How do social movements affect the development and diffusion of new organizational forms? This article theorizes and probes the plausibility of five mechanisms: 1) shaping state administrative regulation 2) entrepreneurship for the purpose of modeling 3) regulating market actors through competition and brokerage 4) developing and disseminating new technologies and 5) conducting scientific research on the efficacy and safety of new and existing technologies, products and services. It provides evidence for the role of these mechanisms in the creation and diffusion of non-hospital abortion clinics in New York City between April 1970, when the state of New York legalized early "on-request" abortions, and January 1973, when the U.S. Supreme Court legalized such abortions nationwide